PCR based detection of gyrB2 gene from Pseudomonas sp. affected human clinical isolates (International Current Pharmaceutical Journal, 2012)
Detection of virulence gene is a key component in determining the pathogenicity of any isolates because these genes act multi-functionally and multi-factorially. Gyrase specific gene primer in combination of PCR technology allows precise detection of DNA gyrase subunit B2 gene (gyrB2) from different virulent microorganisms. In the present study, forward and reverse primers with a length of 20bp for both were used for detection of gyrB2 genes in clinical isolates of Pseudomonas sp. collected from patients suffering from urinary tract infection (UTI). A total of 12 isolates of Pseudomonas sp. viz., Ps1, Ps2, Ps3, Ps4, Ps5, Ps6, Ps7, Ps8, Ps9, Ps10, Ps11 and Ps12 were used in present study in which gyrB2 gene amplified in all 12 isolates and gave the expected 1130bp PCR product after visualization under gel documentation system in 1.2% agarose gel. This PCR was outstanding in the detection of gyrB2 gene in urinary tract infected patients caused by Pseudomonas sp. species.DOI: http://dx.doi.org/10.3329/icpj.v1i9.11612 International Current Pharmaceutical Journal 2012, 1(9): 235-238